(untitled) (Journal of Economics and Sustainability, 2025)
The increasing burden of student debt, particularly within higher education institutions, presents a significant challenge for both students and funding institutions. This study seeks to identify the factors that contribute to students’ inability to repay their academic fees at Universiti Utara Malaysia. With cross-sectional survey of part -time students, this study analyses the likelihood of fee arrears based on student demographic factors – gender, gender, cumulative grade point average (CGPA), employment status, and marital status. This result of study shows that students with tuition fee arrears are ranging from RM1001 to RM 2000, most likely to be male and married with several years of working experience. By means of binary logistic regression, this study sheds light on how these characteristics influence the repayment behaviour, offering insights for targeted financial interventions. These results contribute strategic recommendation for educational institutional to address student debt effectively and refining financial aid repayment policies.